A novel electromagnetic energy harvester based on the bending of the sole. (15th May 2022) - Wang, Suo; Miao, Gang; Zhou, Shengxi; Yang, Zhichun; Yurchenko, Daniil
Highlights: A novel shoe-mounted harvester utilizing the bending of the sole is presented. The working principle is explained and a theoretical model is provided. Average output power around 10 mW at the walking speeds ranging from1 km/h to 7 km/h is obtained. Abstract: Converting mechanical energy into electrical energy during human walking can power the portable electronic devices applied in navigation, gait monitoring, and biofeedback, etc. This paper presents a novel electromagnetic energy harvester based on the bending of the sole to provide electric energy to portable sensors and small devices. The harvester mainly consists of a four-bar linkage, a one-way clutch, a propeller shaft, two bevel gears, a gearbox, and a brushless DC electromagnetic generator, which can covert the bending motion of the sole into the unidirectional rotation of the generator shaft. Then the generator will rotate and generate electrical energy (DC). A prototype is fabricated to demonstrate the feasibility and the practical application of the harvester, and the working principle is explained. The output voltage and output power at different walking speeds are acquired and analyzed. Numerical and experimental results demonstrate that the presented harvester works well and has considerable output power at human normal walking speeds. For a 72 kg test person, the presented harvester can effectively work at the walking speeds ranging from 1 km/h to 7 km/h with the average output power around 10 mW, which is high enough to power low-powered portable devices. The average power density is about 0.43 mW/cm 3, 0.42 mW/cm 3 and 0.2 mW/cm 3 at the walking speed of 4 km/h, 6 km/h and 8 km/h, respectively. Overall, this research may provide a new way and framework to design high-efficiency energy harvesters used for human motion energy harvesting.